Da questa parte del mare. Gianmaria Testa ed Erri De Luca nel secolo delle migrazioni (Altre Modernità, 2009)
Gianmaria Testa's album Da questa parte del mare (2006) expresses a fifteen-year-long meditation about the theme of the great migrations which have marked the Twentieth Century. That same theme is considered by Erri De Luca as the only possible, epic narration of the contemporary world. On the one hand, Testa's project finds its starting point from the song-writer's capacity of observing and interpreting common stories as well as from his considerations about the changing of History; on the other hand, it takes origin from the reading of Erri De Luca's novels and lyrics, especially those of Solo andata. Righe che vanno troppo spesso a capo (2005). Within Testa's Da questa parte del mare, their lyrical voices and artistic and human perspectives seem somehow to cross and melt. Through his songs, Testa tells in an original way the new human geography traced by the migrant phenomenon across the Mediterranean and Europe.